All in the Family: The In-House Honorifics of Lewis and Clark - Arlen J. Large (Names, 1994)
Abstract During the Lewis and Clark expedition, landscape features were named for all 33 people who made the round trip to the Pacific. Names were sometimes linked to events involving party members, but more often they seemed to be assigned randomly. Early re-visits by expedition veterans helped some of these names to survive.